Implementation of hospital‐wide reform at improving access and flow: Impact on time to antibiotics in the emergency department. (17th December 2015) - Roman, Cristina P; Poole, Susan G; Dooley, Michael J; Smit, De Villiers; Mitra, Biswadev
Abstract: Introduction: ED overcrowding has been associated with increased mortality, morbidity and delays to essential treatment. It was hypothesised that hospital‐wide reforms designed to improve patient access and flow, in addition to improving ED overcrowding, would impact on clinically important processes within the ED, such as timely delivery of antibiotics. Methods: A single pre‐implementation and post‐implementation prospective cohort study was conducted prior to and after a hospital‐wide reform (Timely Quality Care (TQC)). Among patients who had intravenous antibiotics prescribed in the ED, data were prospectively collected on times of presentation, prescription and administration of antibiotics. Demographics and discharge diagnoses were retrospectively extracted. Results: There were 380 cases included with 179 cases prior to introduction of the TQC model and 201 cases after its introduction. Time from presentation to administration of antibiotics improved significantly from 192 (99–320) min to 142 (81–209) min ( P < 0.01). The time from presentation to prescription pre‐TQC and post‐TQC was 120 (51–230) min and 92 (49–153) min, respectively ( P < 0.01). The times from prescription to administration pre‐TQC and post‐TQC were 43 (20–83) min and 34 (15–66) min, respectively ( P = 0.03). Conclusion: Following implementation of hospital‐wide reform directed at mitigating ED overcrowding through improved access and flow, times to administration of antibiotics were significantly reduced. These findings suggest that improved quality of care in this area may be achieved with processes aimed at improved hospital access and flow. Ongoing evaluation and vigilance is necessary to ensure sustainability and drive further improvements.